Mapping of the silver coat colour locus in the horse - Brunberg, Emma (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2006)
The silver dappled colour in horses is controlled by a dominant allele that dilutes the black pigment eumelanin. A black or brown horse that carries the allele becomes diluted in mainly mane and tail, while the hair of the body remains dark. The silver dapple colour is common in the Icelandic horse population and has also been observed in for example Shetland pony, Norwegian nordland, Rocky Mountain pony and Ardenne. The purpose of this project has been to try to map and characterise the silver dapple coat colour locus in the horse genome. This has been done by performing a linkage analysis with markers throughout the genome and a marker near a candidate gene; SILV at Equus Caballus chromosome 6 (ECA6). SILV is coding for a protein called Pmel17 that is involved in the production of eumelanin. The gene has been shown to control colour-diluting processes in mouse, chicken and dog. A half-sib family consisting of one Icelandic stallion, 34 of his offspring and 29 of their mothers were used (five offspring shared mother with another offspring). Seventeen of the offspring had the silver colour. Significant linkage was found between the silver phenotype and the marker TKY284 near the SILV gene. The six last exons and introns were sequenced and SNPs were found in intron 9/10 and in exon 11. The nucleotide substitution in exon 11 changes the second amino acid in the cytoplasmic region from an arginine to a cysteine and the same mutation is found in one type of hypopigmented chicken. Twenty-five silver horses from three breeds and 55 non-silver individuals were genotyped for the mutation and this showed a full association with the phenotype. These data shows that SILV probably is responsible for the silver dapple phenotype in horses. The cytoplasmic region of the protein is well conserved among vertebrates. The remaining parts of the SILV gene will be sequenced to search for more mutations and the mutation in exon 11 will be transfected into cell-lines to see how it affects the protein function. Of the pigment genes ...